Fronteiras entre o regional e o transnacional na política de desenvolvimento econômico do Brasil e o caso da fábrica Cyrilla de Santa Maria,RS, Brasil - Lima, Bruna (2019)
This thesis deals with the brazilian economic development policy and the way in which it enabled the entry of transnational beverage companies in Brazil, from restrictions on the national industries, whose owners were mostly immigrants from Axis countries during the World War Two (1939-1945). These restrictions began in the period of authoritarianism, which included the Estado Novo in Brazil (1937-1945), and can be verified through the break-up episodes in 1942, which occurred in several brasilian cities, including Santa Maria, RS, from the legislation that regulated the production and trade of beverages in Brazil, based on internal and external interests, identified by the government and the groups that supported it. This policy culminated in the drafting of Decree Law No. 5,823, of November 14, 1972, precisely when, once again, Brazil experienced a historical moment, marked by interventionism and authoritarianism, post-Goup of 1964, and when laws and decrees involving the production and trade of beverages in Brazil were again the subject of discussions. Based on a qualitative analysis, the investigation of the case of Cyrilla Factory, Santa Maria, enabled us to prove how this type of policy was practiced, expanding national boundaries and demonstrating how local / regional issues reflect and are interconnected to projects hybrids of government and the interests of certain social groups. In this sense, pan-americanism and internationalism had an impact and influenced the political conduct and actions of the government, in both moments, having a continuity in relation to the form of political construction, mainly in relation to the economic development that presented itself as an element as a way of organizing class interests, or as an alternative to justify repressive actions that occurred in both periods, represented by processes of nationalization and institutional acts, respectively, bringing Brazil closer to United States. This research was carried out with the Doctoral Degree in History of the Post-Graduate Program in History, Federal University of Santa Maria (PPGH / UFSM), in the Research Line "Frontier, Politics and Society" and counted on Social Demand scholarship and Doctoral Sandwich abroad, both granted by CAPES..